1H PFG‐NMR Diffusion Study on a Sequence‐Defined Macromolecule: Confirming Monodispersity. Issue 18 (29th August 2019) - Guo, Xiaoai; Wetzel, Katharina S.; Solleder, Susanne C.; Spann, Sebastian; Meier, Michael A. R.; Wilhelm, Manfred; Luy, Burkhard; Guthausen, Gisela
Abstract: A monodisperse decamer bearing ten different side chains, obtained via the iterative Passerini three‐component reaction and subsequent deprotection, is investigated by 1 H pulsed field gradient (PFG) NMR. Both the stimulated echo (PFG‐STE) and a fast spin‐echo pulse sequence (β‐PFG‐SE) are applied to explore the translational diffusion properties of the sequence‐defined decamer in solution at different concentrations with the aim of establishing an independent and new method to confirm its monodispersity. The signals decay according to the expectation of monodisperse molecules in solution with a high experimental accuracy, indeed verifying the monodispersity of these decamers. The diffusion coefficients can further be interpreted in terms of molecular weight. Both NMR methods result in comparable diffusion coefficients, while the β‐PFG‐SE reduces the experimental time by a factor of about 18. Abstract : Monodispersity of a sequence‐defined decamer and its translational diffusion properties in solution are explored by 1 H pulsed field gradient stimulated echo (PFG‐STE NMR) and a modified fast spin‐echo (β‐PFG‐SE NMR). They allow for confirmation of monodispersity and determination of molecular weight of sequence‐defined macromolecules.